The impact of Foreign Direct Investment on poverty in Algeria 1990-2019 - Bouabdallah, Messaoud; Baroudi, Naima (Finance and Business Economies Review, 2022)
The research paper aimed to study the impact of Foreign Direct Investment (FDI) on Poverty in Algeria during the period 1990 to 2019, where the following variables were used: Foreign Direct Investment, Inflation Rate, Trade Openness rate and Per Capita GDP as an indicator for Poverty rate in Algeria. In the long term using the Auto-Regressive Distributed Lag (ARDL) model. The results the study concluded that foreign direct investment had a very weak positive and significant impact on poverty rates in Algeria during the study period